The Application of The Co-op Type Cooperative Learning Model Viewed from Learning Independence - Muhammad Farid Nasrulloh; Erika Dwi Ratnasari; Fitri Umardiyah; Faisol Hidayatulloh (SCHOOLAR: Social and Literature Study in Education, 2024)
The implementation of the co-op co-op type cooperative learning model is seen from the independence of learning Islamic religious education (PAI) material at NU Al-Hidayah Ngimbang Vocational School. This research aims to find out and develop how to implement the co-op co-op type cooperative learning model in terms of independent learning of Islamic religious education (PAI) material at NU Al-Hidayah Ngimbang Vocational School. This research uses quantitative methods with a pre-experimental research design with a one group pre test & post test design. This application makes it easier for students to learn about independent learning through Islamic religious education (PAI) materials. The indicators of learning independence are 1) Initiative and intrinsic learning motivation, 2) Habit of diagnosing learning needs, 3) Setting learning goals/targets, 4) Monitoring, organizing and controlling learning, 5) Viewing difficulties as challenges. This research concludes that the implementation of the co-op co-op type cooperative learning model is effective in terms of independent learning of Islamic religious education material.